On applications of quasi-Abelian Cayley graphs to Denial-of-Service protection - Girejko, Ewa; Malinowska, Agnieszka (Bulletin of the Polish Academy of Sciences. Technical sciences, 2024)
This paper addresses the problem of designing secure control for networked multi-agent systems (MASs) under Denial-of-Service (DoS) attacks. We propose a constructive design method based on the interaction topology. The MAS with a non-attack communication topology, modeled by quasi-Abelian Cayley graphs subject to DoS attacks, can be represented as a switched system. Using switching theory, we provide easily applicable sufficient conditions for the networked MAS to remain asymptotically stable despite DoS attacks. Our results are applicable to both continuoustime and discrete-time systems, as well as to discrete-time systems with variable steps or systems that combine discrete and continuous times.